Influence of occlusal plane inclination and mandibular deviation on esthetics - Cristiane Cherobini Dalla Corte; Bruno Lopes da Silveira; Mariana Marquezan (Dental Press Editora, 2015)
Objective:The aim of this study was to assess the degree of perception of occlusal plane inclination and mandibular deviation in facial esthetics, assessed by laypeople, dentists and orthodontists.Methods:A woman with 5.88° of inclination and 5.54 mm of mandibular deviation was selected and, based on her original photograph, four new images were created correcting the deviations and creating more symmetric faces and smiles. Examiners assessed the images by means of a questionnaire. Their opinions were compared by qualitative and quantitative analyses.Results:A total of 45 laypeople, 27 dentists and 31 orthodontists filled out the questionnaires. All groups were able to perceive the asymmetry; however, orthodontists were more sensitive, identifying asymmetries as from 4.32° of occlusal plane inclination and 4.155 mm of mandibular deviation (p< 0.05). The other categories of evaluators identified asymmetries and assigned significantly lower grades, starting from 5.88° of occlusal plane inclination and 5.54 mm of mandibular deviation (p< 0.05).Conclusion:Occlusal plane inclination and mandibular deviation were perceived by all groups, but orthodontists presented higher perception of deviations.